The Relation between Morphology of Maxillary Sinus after Augmentation in Three Classification Methods and Residual Bone Height: A Retrospective Study - Zhi Wang; Qi Jia; Heng Bo Jiang; Jianmin Han; Lidong Zou; Guangliang Niu (International Journal of Clinical Practice)
Maxillary sinus augmentation is critical to oral implantology, particularly in some cases. The morphology of the sinus floor reflects the lifting effect to a certain extent; however, there has been limited research on the morphology after sinus augmentation. The present study aims to investigate the relationship between residual bone height (RBH) and the morphology of the sinus floor and determine whether a correlation exists between the different evaluation classifications. Maxillary sinus floor augmentation procedures were performed in 56 patients and 68 teeth using the sinus crest approach (SCA). Imaging results obtained after one year of sinus augmentation were analyzed and simultaneously classified along the coronal plane, the sagittal plane, and the biplane (coronal-sagittal). The higher the RBH, the closer the result tends to be to A, A’, or type 1 (more satisfactory). There was a significant correlation between the three different evaluation classifications (p<0.05). The morphology of perforation cases was involved in types C, D, C’, and D’. A more satisfactory post-lifting morphology (tent type and flat type) is probably related to an optimal preoperative bone height, and an unsatisfactory post-lifting morphology is related to a low preoperative sinus floor height. The sagittal plane evaluation correlates with the coronal plane and biplane evaluation and is thus more recommended.